THE THE INFLUENCE OF PRODUCT VARIETY, DISPLAY LAYOUT, AND PACKAGING ON CUSTOMER PURCHASE INTENTION OF MSME AT PERUMDA BIDADARI GALLERY - Hersanius Kurnia Peong; Andy Iwan Iswanto; Fitri Ciptosari; Aurelia Jessica Putri; Aloysius Gonsaga; Yuvensius Adevanli Genggo; Gerardus Kutrisman Trionistan (Pusat Penelitian dan Pengabdian Politeknik eLBajo Commodus, 2023)
Abstract This study aims to analyze the effect of Product Variety, Display Layout, and Packaging on Purchase Intention of Perumda Bidadari UMKM Gallery. By using a descriptive explanatory research approach, data collection was carried out through observation, questionnaires, and interviews with visiting tourists. The data analysis technique uses multiple linear regression, T, F hypothesis testing, and correlation coefficient testing on data processed with the SPSS 26 program. The results of multiple linear regression show that Display Layout (X2) and Packaging (X3) have a significant influence on Purchase Intention (Y), while Product Variety (X1) is not significant. The T test confirms that Display Layout and Packaging have a significant influence, while Product Variety is not significant in predicting Purchase Intention. The F-test results show that the overall regression model is statistically significant with variance in Purchase Intention. The coefficient of determination of 74.5% indicates how much of the variability in Purchase Intention can be explained by the three variables together. This analysis confirms that Display Layout and Packaging have a significant role in influencing Customer Purchase Intention at Perumda Bidadari's MSME gallery. While Product Variety, although not statistically significant, remains relevant in certain contexts.